2016
DOI: 10.1590/s1806-92902016000500001
|View full text |Cite
|
Sign up to set email alerts
|

Use of probiotic-supplemented diet on a Pacific white shrimp farm

Abstract: -The objective of this study was to evaluate the use of a diet supplemented with Lactobacillus plantarum on performance, immunological parameters, and bacterial microbiota of the digestive tract of white leg shrimp (Litopenaeus vannamei). We used six earthen ponds (1.2 ha) stocked with 14 shrimp m −2 (3 g mean weight). Three ponds received a diet supplemented with L. plantarum and three were maintained as control. The survival and feed efficiency of shrimp fed the supplemented diet were greater than that obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 21 publications
0
17
1
3
Order By: Relevance
“…Several studies have reported on the benefits of Lactobacillus in resisting some pathogens in fish. L. plantarum, Lactobacillus, and Carnobacterium strains isolated from rotifer can limit the density of some Vibrio species which causes disease in flounder larvae in the shrimp gut [45,46]. Moreover, L. plantarum is one of the important species used in fermenting several foods and can also release antibacterial substances that prevent some pathogens, such as plantaricin [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported on the benefits of Lactobacillus in resisting some pathogens in fish. L. plantarum, Lactobacillus, and Carnobacterium strains isolated from rotifer can limit the density of some Vibrio species which causes disease in flounder larvae in the shrimp gut [45,46]. Moreover, L. plantarum is one of the important species used in fermenting several foods and can also release antibacterial substances that prevent some pathogens, such as plantaricin [47].…”
Section: Discussionmentioning
confidence: 99%
“…Yet another study [23] indicated that the survival of black tiger shrimps improved from 20% to 87% as shrimps were fed diet supplemented with Lactobacillus and challenged with V. alginolyticus for 10 days. It was reported that the diet mixed with L. plantarum enhanced the immune system, as well as the digestion ability of whiteleg shrimps [45], resulting in higher survival rates of challenged shrimps.…”
Section: Discussionmentioning
confidence: 99%
“…En la actualidad, numerosas cepas bacterianas del género Bacillus se utilizan como probióticos para promover el crecimiento en organismos acuáticos cultivados (Kumar et al, 2016;Ringø y Song, 2016), especialmente en estadios larvarios (Newaj-Fyzul et al, 2014;Vieira et al, 2016;Zorriehzahra et al, 2016). De esta manera, se ha descrito previamente el efecto de cepas de B. firmus como promotores del crecimiento y supervivencia en el camarón blanco (Litopenaeus vannamei) (Yuniarti et al, 2013;Barman et al, 2017), una especie de interés comercial que actualmente se ve afectada por enfermedades bacterianas, especialmente durante las etapas larvarias (Flores-Miranda et al, 2012;López León et al, 2016).…”
Section: Introductionunclassified
“…(Najmi et al, 2018), los cuales son utilizados como alimento vivo en el cultivo de organismos acuáticos en estadios larvarios (Gatesoupe, 1991;Hirata et al, 1998;Zink et al, 2013). En consecuencia, la creciente demanda en la bioseguridad en la cadena de producción, ha exigido el uso de estrategias biotecnológicas que eviten el uso inadecuado de antibióticos, y que permitan mejorar la respuesta fisiológica en los estadios larvarios y postlarvarios de especies como el camarón blanco, así como la calidad y los parámetros de los cultivos de rotíferos (Vieira et al, 2016;Li et al, 2017). Por consiguiente, el presente estudio presenta las características de B. firmus C101 como promotor del crecimiento y posible candidato probiótico para poslarvas de camarón blanco (L. vannamei), y en el cultivo de rotíferos (B. plicatilis s.s.).…”
Section: Introductionunclassified
See 1 more Smart Citation